Book Review: Client Psychology (Journal of Financial Therapy, 2019)
For practitioners and researchers in the field of financial therapy, the interweaving of emotion and money has been at the center of our attention since the field’s inception (Grable, McGill, &Britt, 2010). The field of financial planning, a field in its 50th year (Brandon& Welch, 2009) is making active steps to include this same realization in the Center for Financial Planning’s edited book, Client Psychology. The work, edited by Dr. Charles Chaffin, the director of academic programs and initiatives for the CFP® Board, brings together important chapters that begin to prepare financial planners for integrating client psychology into their practices.
Keywords: client psychology; financial therapy; financial planning